Classifications and tasks of green areas in the contemporary town - Kłopotowski, Maciej (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2016)
The second part of research on the classification of green areas in the city is devoted to defining the featuresand tasks of distinguished landscape architecture objects. The characteristics of individual objects have been defined by the division into the issues of: the availability of the site, its utility function and , the way it’s been equipped. The tasks have been determined on the basis of the modern theory of this subject. The conclusion shows the summary results of research.